Size-Resolved Elemental and Optical Measurements of Greenland GEOSummit Aerosols 2003 to 2020 - Nicholas Spada; Thomas Cahill (Arctic Data Center, 2021)
In 2003, University of California Davis was asked to design and implement an aerosol sampling and analysis program capable of providing continuous, year-round aerosol data while handling the extreme conditions at the Greenland Summit site, including burial in an under-snow container for a month at a time. The method we chose uses a slowly rotating multi-stage impactor (Davis Rotating-drum Unit for Monitoring, DRUM, (Cahill et al., 1985)) to collect aerosol samples, developed and applied earlier in Aerosol Characterization Experiments (ACE) Asia. This unit was compared with standard Federal Reference Method PM2.5 mass with excellent results (Cahill et al., 2014). The DRUM provides data at user-specified temporal resolution (e.g., 3-hour, 12-hour, 24-hour) in eight distinct size bins from 10 to 0.9 micron diameter (Raabe et al., 1988) and over extended periods (e.g., 44 weeks). To perform the compositional analysis, synchrotron induced X-ray fluorescence (SXRF) based at the Berkeley (Advanced Light Source) and Stanford (Stanford Synchrotron Radiation Light Source) facilities, with sensitivities for transition elements in the sub-picogram/cubic meter range (Jenniskens et al., 2012) Elements analyzed include: Na, Mg, Al, Si, P, S, Cl, K, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, As, Se, Br, Rb, Sr, Y, Zr, Mo, and Pb. In 2021, Beamline 1B was developed at Crocker Nuclear Lab (UC Davis) to analyze light elements (Na to Fe) using Proton Induced X-ray Emission (PIXE) as well as bound hydrogen using Proton Elastic Scattering Analysis (PESA). The light elements, especially P, S, Cl, and K, aid identification of dust sources, as shown in (Seinfeld et al., 2004).